Metode Identifikasi MaqÃ¢sid al-SharÃ®âah Muhammad TÃ¢hir b. âÃshÃ»r dalam Kitab MaqÃ¢sid al-SharÃ®âah al-IslÃ¢mÃ®yah - Aziz, Muhammad (MarÃƒÂ¢ji`: Jurnal Ilmu Keislaman, 2014)
This article attempts to analyze how to know maqÃ¢sid al-shariâah in any statutes of shariâat with Muhammad TÃ¢hir b. âÃshurâs perspective in the book of MaqÃ¢sid al-SharÃ®âah al-IslÃ¢mÃ®ya. This study concludes that the formula of turuq ithbÃ¢t maqÃ¢sid al-shariâah in the perspective of Ibn âÃshur refers to three ways: first, through istiqrÃ¢â (inductive), be it istiqrÃ¢â on the known-rationale laws, or istiqrÃ¢â to the postulates of the law which has the same substantive rationale (mushtarak fÃ® al-âillah), in which the existence of the rationale qualify as maqsÃ»d al-ShÃ¢riâ; second, through the verses of the Quran which has the clarity of the arguments (wÃ¢dih al-dilÃ¢lah); and third, through the text of Sunnah mutawÃ¢tirah, either mutawÃ¢tir âamalÃ® or mutawÃ¢tir maânawÃ®.